Kompetensi sosial sebagai prediktor kesuksesan berwirausaha pada pemilik kafe food & beverage di wilayah Kecamatan Dau Kabupaten Malang - Kristha, Jefa Lavidhatiya (Universitas Negeri Padang, 2023)
Abstract : The purpose of this research is 1) to know the description of social competence and entrepreneurial success, 2) to examine the magnitude of the contribution of social competence to entrepreneurial success in food and beverage cafe owners in the Dau area, Malang district. This study uses a non-experimental quantitative effectual method. With a sample of 50 food & beverage cafe owners in the Dau sub-district, Malang district, selected by purposive sampling technique. The instruments used are the scale of social competence and the scale of entrepreneurial success. The data analysis used is descriptive analysis and simple linear regression analysis. The results of the analysis show that the majority of food & beverage cafe business owners have moderate categories of social competence and entrepreneurial success. And there is an influence of social competence on entrepreneurial success of 12.9% with a positive direction of influence. From this research, it is expected that food & beverage cafe business owners will have positive self-esteem, need to socialize, and expand cooperative relationships with the aim of increasing the success of a business. Future researchers can examine other psychological factors and distribute the subject evenly.